Investigation of stimulated brillouin scattering for the generation of millimeter wave for radio over fiber system - Mohamed Nawawi, Norizan (2008)
Radio over fiber (ROF) systems is characterized by having both a fiber optic link and free-space radio path. Such systems are important in a number of applications, including mobile communications, wireless local area networks (LANs), and wireless local loop, etc. However, the growing demand for higher data rates in wireless communication systems requires new frequency bands. The millimeter-wave (mmwave) range has the highest potential here because it is currently uncluttered and can support high data bandwidth. To ease system complexity in such systems there is growing interest in the exploitation of photonic technologies for the distribution of the mm-waves from a central station to a number of base stations via optical fiber links. Several techniques have been proposed for the optical generation of mm-waves such as direct modulation, external modulation, optical heterodyning and so on. However, in this work we proposed and investigate an alternative to above mention methods, which is based on Stimulated Brillouin Scattering (SBS) in an optical fiber. SBS technique was designed and modeled by performing CW laser in a single mode optical fiber (SMF) through optical Mach-Zehnder modulator (MZM) with two pump lasers for amplification purposes. The analysis was done by determination of the power depletion of generated. SBS performance with the optical fiber loop length up to 100km was analyzed. It has been shown that SBS power is depends on the fiber loop length which is higher and lower at certain length due to natural properties of the fiber. The design shown the RF generation was achieved up to 60 GHz.